ANALISIS PERKEMBANGAN DAN DAMPAK PARIWISATA DALAM MASA PANDEMI COVID-19 TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN SAMOSIR - Rikawati Ginting; Vina Maria Ompusunggu (JURNAL REGIONOMIC, 2022)
The tourism sector is still a priority sector for the government because it is considered capable of being the locomotive of the nation's economic movement. The management of the tourism sector continues to be developed by the government, through various policies carried out by the government to make Indonesian tourism more advanced and known in the eyes of the world. The role of the national tourism sector is increasingly important in line with the development and contribution made by the tourism sector through foreign exchange earnings, economic growth, regional income, regional development, as well as in the absorption of investment and labor as well as business development spread across various regions in Indonesia, especially in Kabupaten Samosir, North Sumatra. Entering the end of 2019, the world was rocked by the Covid-19 pandemic to various countries in the world, including Indonesia, especially the Samosir Regency which had a huge impact on the world's economic sector in the tourism sector. Tourism contributes to economic growth through various channels, including foreign currency earnings, attracting international investment, creating jobs, and so on. This writing aims to examine literature from various sources, such as news in the mass media, relevant research results, and government policies. Data analysis was carried out with a qualitative-interpretive look at the development of tourism and the phenomenon of tourism conditions during the COVID-19 pandemic in Samosir Regency. Collecting data in this study using interviews, observations and documentation. Data analysis in this study used data reduction, data presentation and conclusion drawing. The results of the development and impact of tourism during the COVID-19 pandemic on economic growth show that the government has provided special policies in order to improve the tourism sector, and various tourist destinations have also implemented strategies and programs that are able to adapt to conditions called the new normal era. and there is a change in tourist behavior. Therefore, the tourism model in this new normal era can be described, namely, tourism behavior, domestic tourist orientation, government policies, and new tourism programs.